A cross-sectional study of Persian medicine and the COVID-19 pandemic in Iran: rumors and recommendations (2020)
Background: Traditional medicine structures such as Persian medicine (PM) are deeply rooted in the global health system. These modalities, if applied correctly, could help health systems overcome situations such as the coronavirus disease 2019 (COVID-19) pandemic. However, the mismanagement of such traditional structures results in fear, stress, anxiety, and risky behavior among society. The current study aimed to assess the penetration ofthe recommendations and rumors related to PM during the COVID-19 pandemic and the relationships of these recommendations and rumors with related health factors. Methods: In a cross-sectional study performed in March 2020 (during the COVID-19 pandemic) in southern Iran, eligible participants were randomly selected. The participants completed a 29-item online questionnaire assessing different aspects of the rumors and recommendations pertaining to PM linked with the COVID-19 pandemic. Results:Intotal, 523 participants took partinthe survey. Themeanfear score was 65.2/100.Approximately 99% of the study population had heard at least one of the rumors/recommendations of PM related to COVID-19. The average scores of disagreement with the rumors and recommendations linked to PM were 16.4/50 and 18.4/35, respectively. The fear score and the level of disagreement with the rumors were significantly related (p = 0.024). Conclusions: The use of PM might be beneficial in the management of the COVID-19 pandemic provided that a revolution occurs in data sharing. Various approaches should be considered in the management of traditional medicine modalities such as PM during disease outbreaks to help overcome the current dilemma.